Conditions of Seagrass Ecosystems in Gili Sulat Waters, Sambelia District, East Lombok Regency in 2022 - Suhaeri Ihwani; Agil Al Idrus; I Gde Mertha (Jurnal Biologi Tropis, 2023)
Seagrass has high productivity so it is said to be a complex shallow marine ecosystem. The role of seagrass ecosystems is very important, especially in terms of ecological and economic functions. The purpose of this research is to reveal the existing condition of the seagrass ecosystem. Data collection used the line transect method with a square measuring 1m x 1m. The sampling technique uses a systematic random sampling method. The results of the study obtained 4 species and 2 families, among others: Hyddrocharitaceae including Enhalus acoroides, and Thalassia hemprichii. The Potamogetonaceae family consists of Cymodocea rotundata, and Syringodium isoetifolium. Seagrass species that have a high enough influence on seagrass ecosystems in Gili Sulat waters are Thalassia hemprinchii, with an important value index (INP) of 184.74, a density value of 65.59% (rather dense status), a frequency of 48.21% (wide enough distribution), and 70.84% coverage (rich/healthy status).